2019
DOI: 10.1111/aji.13147
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of microbial colonization in cervical mucus of women with and without endometriosis

Abstract: ProblemIntrauterine microbial colonization and its association with the pathogenesis of endometriosis via an innate immune cascade have been reported. As a potential source of microbial transmission, information on microbial colonization in cervical mucus is unknown. We investigated pattern of microbiota in the cervical mucus collected from women with and without endometriosis using next‐generation sequencing (NGS) technology.Method of studyCervical mucus samples were collected from women with (n = 30) and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(102 citation statements)
references
References 46 publications
4
97
0
1
Order By: Relevance
“…Unclear or absent from the full texts in all but one human study was whether study participants were consecutively recruited, permitting the closest representation of patients with endometriosis. Human studies that had an NOS score of ≥6 (out of 8, as the nonresponse rate category was not applicable for these study methodologies) had reliably strong definitions of cases versus controls, appropriate selection of controls, and laparoscopic evidence of endometriosis presence or absence …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Unclear or absent from the full texts in all but one human study was whether study participants were consecutively recruited, permitting the closest representation of patients with endometriosis. Human studies that had an NOS score of ≥6 (out of 8, as the nonresponse rate category was not applicable for these study methodologies) had reliably strong definitions of cases versus controls, appropriate selection of controls, and laparoscopic evidence of endometriosis presence or absence …”
Section: Resultsmentioning
confidence: 99%
“…The various kits and sequencing methods used are outlined in Table . Of the seven studies that used 16S rRNA amplicon sequencing, only five discussed the targeted sequencing region . Each study targeted different regions, including region V3/V4, region V4, region V3–V5, region V4/V5 and region V5/V6 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies have reported the presence of members of phyla Firmicutes, Bacteroidetes, Proteobacteria, and Actinobacteria, among others, as part of "health" uterine microbiota (127)(128)(129), and that changes of this diversity and its abundance are related to alterations in endometrial function (127,130,131), benign uterine pathologies (128,132,133), or endometrial cancer. In the case of endometriosis, changes of taxonomic bacterial composition to potentially pathogen bacteria in patients diagnosed with the disease have been detected in peritoneal fluid, cervical mucus, and cervicovaginal microbiota (129,134,135). However, studies that detect the real changes in endometrial microbiota related to endometriosis are lacking; furthermore, studies carried out to date in general lack a control group with healthy women (without any benign pathology) and face difficulties to obtain endometrial samples, among other technical complications (126,134,136).…”
Section: Contribution Of Inflammation Of Bacterial Origin To Endometrmentioning
confidence: 99%